INITIAL EVALUATION OF THE EFFECTIVENESS OF COMBINED PHYSICAL THERAPY IN THE TREATMENT OF CONSTIPATION IN STROKE PATIENTS AT THE DEPARTMENT OF PHYSICAL THERAPY, 108 CENTRAL MILITARY HOSPITAL, IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of physical therapy in treating constipation in stroke patients at the Rehabilitation Department, 108 Military Central Hospital.Materials and Methods: A prospective, non-controlled clinical intervention study was conducted on 32 stroke patients with constipation symptoms, treated at the Rehabilitation Department, 108 Military Central Hospital from December 2024 to May 2025. Patients received: abdominal massage, pelvic floor and abdominal muscle strengthening exercises, and electrical stimulation of the pelvic floor muscles Results: Among constipated patients, 68.75% had ischemic stroke and 21.25% had hemorrhagic stroke. After intervention, defecation frequency increased from 2.1 ± 0.7 to 4.8 ± 0.9 times/week (p
Keywords: Physical therapy, constipation, stroke, quality of life.